Uji Antagonis Jamur Tempe (Rhizopus Sp) terhadap Bakteri Patogen Enterik - Dewi Peti Virgianti (Fakultas Biologi | Universitas Jenderal Soedirman, 2015)
Indonesian tempeh is a food product made from soybeans fermented by Rhizopus oligosporus. The role of R.oligosporus as the primary fungi in soybean is very important, that changing the composition of the substrate soybeans into food that is more nutritious and contains many enzymes and bioactive compounds, including antibacterial compounds. This study was aimed at testing the antibacterial activity of Rhizopus sp fungus isolated from commercial tempeh against several enteric pathogen bacteria Escherichia coli ATCC 25922, Salmonella typhimurium ATCC 14028 and Shigella flexneri ATCC 12022. The tests were conducted by the antagonism test agar diffusion method, by putting pieces of SDA that has grown Rhizopus sp on agar Muller Hinton which test bacteria was inoculated. The incubation period was 24 hours at 37 ° C. The results showed that Rhizopus sp has antagonistic to the bacteria, which produce inhibitory zone of 28 mm against the E.coli ATCC 25922, 26 mm against S.typhimurium ATCC 14028 and 39.5 mm against Shigella flexneri ATCC 12022. Based on these results it can be concluded that the Rhizopus sp isolated from tempeh is antagonistic against enteric pathogenic bacteria. The results of this study reinforce the benefits of tempeh as a functional food.